Colonus and Lampedusa: The Tragedy of the Border and the Dialectics of Repair. Issue 1 (2nd January 2018) - Rainey, Mark Justin
Abstract: This article brings together Sophocles's tragedy, Oedipus at Colonus, with an account of the 2013 Lampedusa disaster in which over 300 migrants perished off the coast of Italy. This juxtaposition conflates the ancient and the contemporary in order to draw out a decisive feature of border regimes: they not only produce legal and social ambiguity among migrants, but also attempt to instrumentalise and 'fix' this ambiguity in favour of the receiving state, with often tragic consequences. This article also outlines the possibility of an alternative ethics that takes place outside this unbalanced relation. By drawing on Vicki Squire's notion of 'mobile solidarities' and Gillian Rose's wider political category of 'Ethical Life', it proposes a more grounded and speculative ethics of repair that both affirms ambiguity and disrupts and troubles the statist framing of the migrant.